vicky Penerapan Sistem ATS (Automatic Transfer Switch) sebagai Pengendalian, Pemantauan, dan Perawatan Berbasis IoT (Internet of Things) - Syahrul Pambudi; Vicky Prasetia; Saepul Rahmat (Infotekmesin, 2023)
The need for electricity is increasing along with population growth. The main electricity supply (PLN) is not always continuous in its distribution, so alternative power is needed, namely generators. The ATS (Automatic Transfer Switch) system can transfer the voltage source to the load. The ATS system is equipped with IOT in the form of a Blynk application on Android which functions as a controller and can send ATS damage notifications. This research was conducted to meet the electricity needs. Users can monitor, control and maintain the ATS system in the event of a breakdown. The method in this study uses a quantitative method, namely data collection by testing the ATS system and testing the IOT Blynk application function as a notification of damage to the ATS system. The result of transferring the PLN voltage to the generator is only 7 seconds and 3 seconds vice versa. There was damage to the lamp cable 1 time, the relay 1 time, and the fan cable 2 times. The results of measuring the current and voltage of the PLN source: lamp load 0.02A, 3.4V; fan 0.04A, 3.5V; AC motor 0.04A, 4V. Generator current and voltage measurements are as follows: lamp load 0.02 A, 9.1V; 0.03A, 9V fan; AC motor 0.05A, 4.5V.